Strategi Komunikasi Pemasaran IndiHome Dalam Membangun Positioning Di Tengah Pandemi Covid-19 Di Indonesia - Gan Gan Giantika (Jurnal Komunikasi, 2021)
Abstrak – The marketing communication strategy in building positioning in the midst of the Covid-19 pandemic in Indonesia is research on IndiHome, which is a service product of PT. Telkom Indonesia (Persero) TBK, in Indihome's marketing communication strategy to build positioning in the midst of the Covid-19 pandemic in Indonesia. This study aims to determine the commitment and marketing communication strategy techniques of IndiHome in building positioning in the midst of the Covid-19 pandemic in Indonesia. The methodology used in this research is a qualitative method. The data collection techniques in this study used observation, literature study, documentation study, and internet search. The results of this study indicate that IndiHome, which is a service product of PT. Telkom Indonesia (Persero) TBK, can build a positioning through a marketing communication strategy by launching the #dirumahgaknyerah movement. This movement, which is in line with the government's agenda to reduce activities outside the home, is implemented through several programs such as the Digital Activation #dirumahgaknyerah, AdsQoo Webinar, MaXight Webinar. Positioning strategy is a way to create unique differentiation in the minds of the target market, so that an image of a brand or product is superior to competitors' brands / products. Keywords: Communication Strategy, Marketing Communication, Positioning